The Role of Systematic Safety Analysis in Reducing Occupational Risk in Industry - Dustkabilovich, Rakhimov Oktyabr; Sokhiba, Tulaeva (EDUMALSYS Journal of Research in Education Management, 2026)
This article examines the role of systemic analysis in reducing occupational risk in industrial settings by clarifying the nature of hazards, their types, and the underlying causes of potential hazardous conditions. It aims to explicate the logical development process linking “hazard – cause – unintended consequences,” to illustrate this process through practical examples, and to elaborate on the “Cause and Risk Tree” as a structured tool for identifying and evaluating risk pathways. Using an analytical and conceptual approach, the article systematizes key concepts of hazard and safety, describes the structure and purpose of systemic analysis in safety management, and outlines the logical processes involved in constructing and interpreting cause–consequence relationships. The discussion highlights how the integration of systemic analysis and the Cause and Risk Tree framework enables more comprehensive identification of causal chains and unintended outcomes, thereby supporting targeted risk reduction strategies in industry. The article concludes that a rigorous, system-oriented approach to safety analysis enhances the effectiveness of occupational risk management and provides a methodological basis for improving safety decision-making and preventive measures in industrial practice.